PERAN TUTOR DALAM PEMBELAJARAN KETERAMPILAN DI SKB KOTA AMBON - Claudia Makulua; Rosmarin Tutupary; Junita L. Kundre (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the importance of non-formal education in providing learning opportunities for communities who have limited access to formal education. SKB Kota Ambon plays a strategic role in empowering the community through skills training programs, particularly culinary skills. This research aimed to describe the role of tutors in skills learning at SKB Kota Ambon. The study employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews with tutors and learners, and documentation. The results revealed that tutors performed three main roles. As informators, tutors prepared systematic learning materials based on lesson plans and modules and applied demonstration and hands-on practice methods to facilitate learners’ understanding. As motivators, tutors created an engaging learning atmosphere, provided encouragement, and built learners’ self-confidence through positive reinforcement and varied teaching strategies. As evaluators, tutors conducted continuous assessments through direct observation of practice, provided constructive feedback, and offered remedial guidance for learners who had not yet achieved the expected competencies. The study concludes that the success of skills learning at SKB Kota Ambon is strongly influenced by tutors’ competence and commitment in carrying out their roles as informators, motivators, and evaluators in an integrated manner.